2005
DOI: 10.1098/rspb.2004.3036
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive significance of avian beak morphology for ectoparasite control

Abstract: The beaks of Darwin's finches and other birds are among the best known examples of adaptive evolution. Beak morphology is usually interpreted in relation to its critical role in feeding. However, the beak also plays an important role in preening, which is the first line of defence against harmful ectoparasites such as feather lice, fleas, bugs, flies, ticks and feather mites. Here, we show a feature of the beak specifically adapted for ectoparasite control. Experimental trimming of the tiny (1-2 mm) maxillary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
103
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(105 citation statements)
references
References 30 publications
(43 reference statements)
1
103
0
1
Order By: Relevance
“…Clayton et al [125] demonstrated how the maxillary overhang functions to control lice. Experimental removal of the tiny (1-2 mm) overhang (Fig.…”
Section: Grooming: Self-preeningmentioning
confidence: 99%
See 2 more Smart Citations
“…Clayton et al [125] demonstrated how the maxillary overhang functions to control lice. Experimental removal of the tiny (1-2 mm) overhang (Fig.…”
Section: Grooming: Self-preeningmentioning
confidence: 99%
“…importance of the maxillary overhang for controlling lice, Clayton et al [125] concluded that the adaptive radiation of beak morphology in birds should be re-assessed with both feeding and preening in mind.…”
Section: Grooming: Self-preeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, morphologies of avian bills and claws may partially reflect adaptations to combat lice. Several birds have slightly hooked upper mandibles, and this small, curved upper bill overhang is essential for the efficient preening to control ectoparasites (Clayton et al, 2005). Similarly, some avian taxa possess pectinate claws, potentially increasing efficacy of scratching against lice (Bush et al, 2012).…”
Section: The Bird-louse Relationshipmentioning
confidence: 99%
“…The feather damage they cause has thermoregulatory costs that lead to reductions in host fitness (18). Birds defend themselves against feather lice by destroying or removing the lice with their bill during frequent bouts of preening (19).…”
mentioning
confidence: 99%